Simulation, fabrication and electrical characterization of p-Si capacitor design structure - Cheryl She Siew Yuet (Universiti Malaysia Perlis, 2008)
Technology CAD (TCAD) refers to the use of computer simulation to model semiconductor processing and device operation. TCAD has two major functions which are process simulation and device simulation. It performs the semiconductor process simulation function and the device simulation function by taking the description of the capacitor input to simulate the fabrication process and device behavior before the actual silicon is made. The objectives and scopes of this work are to demonstrate the application of Synopsys TCAD Tools in developing p-Si capacitors fabrication process. In developing the p-Si capacitor, there are few areas to focus such as simulation process, fabrication specification and electrical characterization of the device. This Final Year Project report illustrates the use of Synopsis Taurus TCAD to develop process simulation (TSUPREM-4) and device simulation (MEDICI) to obtain the parameter used for fabrication process. The device will fabricated using standard semiconductor processing technique. The masks for fabrication are designed in AutoCAD tool and print on high quality of transparency with aid of photo plotting technique. The final product of the fabricated device will be gone through an electrical characterization testing by Semiconductor Parametric Analyzer to get the CV curve. Simulation and electrical characterization result will be compare with 10 µm and 100 µm gate area size and there are percentage error occur. The percentage error of oxide thickness (0.238 %), voltage breakdown is less than 9 %, threshold voltage 0% and oxide capacitance is around 20%. As conclusion, the objective of this work was achieved where all the parts were successfully conducted and obtain the result. Also consist of recommendation to enhance the project such as provide in the equipment which also can characterize high frequency capacitance.